Deconvolution: An analysis of theses and dissertations and their relevance to the nuclear area in Brazil (Research, Society and Development, 2025)
Convolution and deconvolution (inverse convolution operation) are mathematical methods used for processing signals and images, and can be applied in different areas of knowledge, such as Astronomy, Geology, Mathematics and Medicine. The present paper aimed to verify or even demonstrate the relevance and analyze, through the management of scientific knowledge, the study of mathematical methods in different areas of knowledge and, in particular, in research in nuclear energy field through a survey in the Bank of Theses and Dissertations (BTD) of the Coordination for the Improvement of Higher Education Personnel (CAPES). A bibliometric research of a quantitative nature was carried out. It is understood that, although few studies were found in the nuclear area, the use of the deconvolution process is evolving, considering its importance for spectrometry analyses, mainly for Metrology, an activity that is extremely relevant for the country.